MODEL BISNIS DAN PENGUNGKAPAN RISIKO PERUSAHAAN - Totok Dewayanto (STIE Pelita Nusantara Semarang, 2020)
The aim of this study is to examine business model on disclosure of corporate risk. This study uses Size as a control variable. The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2015 - 2017. Sample determined with purposive sampling method. Total sample of this research is 180 companies. This study used multiple regression analysis for hypotheses testing. The results of this study show that business model has positive effect and significant on corporate risk disclosure.